A Clash of Two Generations: A Comparative Deconstructive Discourse Analysis of Three News Reports on Megawati’s Critique for Indonesian Millennials - Bima Iqbal Khadafi (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2021)
Written in the spirit of critical tradition, this paper aims to demystify the hegemony induced in the media coverages about the critique of Indonesian former president, Megawati Soekarnoputri, towards its millennials for ‘lacking contribution to the country’. By applying genre, deconstruction and dynamic perspective of ideological tension analyses, this article reveals how three different medias report the phenomenon differently by bringing up different topics to be discussed for their own purposes. While scrutinizing the relationship between the phenomenon and its news reports, this paper sees a need for a transvaluation to the concept of nationalism which in the end negates itself since the conception of nationalism itself has to do with power struggle that has the potential to degenerate the Self and harm the Other.